Phytochemical profile of medicinal Indian spices (Indian medicinal spices) - LOSHITARANI ROY (International Journal of Pharma and Bio Sciences, 2019)
Spices have been used as flavourants and aromatics in Indian food since ancient times. The bio- active natural phytochemical compounds in these spices make them rich source of compounds with varied medicinal properties. The presence of several effective bioactive compound and essential oils has made them an interesting part of research. The presence of such important compounds make them as potent substrate for the formulation of important herbal drugs and herbal medication products. The spices are used in Indian tradition for so long for wound and pain healing. The indian spices are found to possess good antimicrobial and antioxidant property. The research was carried out to study the active compounds of four such spices - curry leaves, bay leaves, hemp seeds and black pepper. The spices sample were sterilized and were used for extract preparation. The extract obatined was undertaken for qualitative analysis of the phytochemical compounds. The analysis revealed presence of several effective phytochemical compound in the extract conferring to their potent biological activity. The extract was subjected to TLC analysis to determine the estimated presence of bioactive compounds and essential oils in them. The TLC analysis undertaken along with the standard compounds and hence the compounds were determined based on their Rf value comparative to the standard compound. The different components detected by thin layer chromatography methods in Curry leaves were α-Amorphene, γ-Eudesmol, β-Pinene, α-Terpinolene, Limonene, (Z)-β-Ocimene. Terpenes, Sesquiterpenes, Eucalyptol, Terpinyl acetate are found in Bay leaves and in Hemp seeds Cannabinol, Tetrahydro cannabinol, Cannabidiol, Tetrahydro cannabivarin, cannabivarin, cannabichromene are found. Black pepper seeds contain Piperine, guineensine, Piper amide and Piperolein b. The further confirmed detection of the compounds was done using HPLC analysis. For this the compounds estimated by TLC were selected and their standards were loaded in the column. Then the extracts were analyzed, based on the chromatogram for standard compound and the extract their presence was confirmed in the extract. The HPLC detection was undertaken with different mobile phases for different extracts. These active compounds can be further explored for their role against pathogenic microorganisms.